Darwin the writer - Levine, George Lewis (Oxford : Oxford University Press, 2011)
Darwin's enormous cultural success depended as much on the construction of his argument and the artistry of his language as it did on the power of his ideas. By exploring Darwin as a writer as well as a scientist, this book transforms our understanding of him, giving us a Darwin who is comic rather than tragic.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Darwin, Charles, -- 1809-1882.; Darwin, Charles, -- 1809-1882 -- Literary art